Adherence of model molecules to silica surfaces: first principle calculations - Nuñez, Matias (2013)
The adherence of model molecules to  crystal SiO2 surfaces is studied from first principle calculations at the DFT level. Adsorption energies are calculated which follow the experimental threads obtained elsewhere (Rivera et al.,2013). We study the quantum nature of the electronic charge transfer between the surface and the molecules, showing the localized and delocalized patterns associated to the repulsive and attractive case respectively.